Efektivitas Pelatihan Bela Negara terhadap Nasionalisme Mahasiswa Universitas Negeri Malang - Tutut Chusniyah; Atok Ahmad Rizqoni; Dedi Kuswandi; I Nyoman Ruja; Gebi Angelina Zahra; Agung Minto Wahyu (Graduate School of Universitas Negeri Malang, 2021)
Abstract: The aim of this study was to determine the effectiveness of state defense training on the nationalism of students at the State University of Malang. The research method used quasi-experimental. The independent variable is state defense training and the dependent variable is nationalism. The research subjects were students of the State University of Malang, totaling 333 people. Subjects were given pre-test and post-test to measure the success of the treatment. The instrument for measuring nationalism uses Blank dan Schmidt. Data analysis used the Wilcoxon signed test. The results of the hypothesis test were proven significantly with a significance value of 0.013. It can be concluded that the state defense training is effective in increasing the nationalism of State University of Malang students.Abstrak: Tujuan penelitian ini untuk mengetahui efektivitas pelatihan bela negara terhadap nasionalisme mahasiswa Universitas Negeri Malang. Metode penelitian menggunakan quasi-eksperimen. Variabel bebas berupa pelatihan bela negara dan variabel terikat berupa nasionalisme. Subjek penelitian merupakan Mahasiswa Universitas Negeri Malang yang berjumlah 333 orang. Subjek diberikan pre-test dan post-test untuk mengukur keberhasilan dari perlakuan. Instrumen untuk mengukur nasionalisme menggunakan skala nasionalisme milik Blank dan Schmidt. Analisis data menggunakan uji wilcoxon signed test. Hasil uji hipotesis terbukti secara signifikan dengan nilai signifikansi 0,013. Dapat disimpulkan bahwa pelatihan bela negara